Attitudes and perceptions of teachers toward mental health literacy: A case of Odzi High School, Mutare District, Zimbabwe - Sibanda, Theresi; Sifelani, Innocent; Kwembeya, Maurice; Matsikure, Memory; Songo, Sifikile (Frontiers in Psychology, 2022)
In dealing with adolescent mental health, teachers and school institutions have a critical role in minimizing the challenges of mental health. However, the success of such a measure is dependent on teachers’ attitudes and perceptions of mental health literacy. Adolescent mental health disorders have become a major global concern with heightened increases and prevalence in secondary schools. In Zimbabwe, a dearth of knowledge exists in understanding the perceptions and attitudes of teachers in maximizing student mental health and positive educational outcomes. The aim of the research was to understand the attitudes and perceptions of teachers toward mental health literacy. Using a qualitative approach to understanding attitudes and perceptions, a case study was carried out at Odzi High School. A total of 12 teachers were purposively sampled for data generation on knowledge, attitudes, perceptions, and strategies that can be used to inform adolescent mental health. Data were collected using semi-structured interview(s). Emergent themes of the study were knowledge, stigma, training, and development. Using thematic analysis, the data showed that there was generalized knowledge of mental health and there were disparities in effective and efficient responses to gender sensitivity issues. Additionally, this knowledge was not put into practice because of attitudes and perceptions toward mental health. Recommendations from the study include developing of mental health training for teachers, equipping teachers with skills in psychosocial support in schools’ mental health, and enabling teachers to be able to link adolescents to appropriate care within the school and community-based settings. Teachers have the responsibility of promoting the wellbeing of the students, thus minimizing the adverse effects. Outcomes for positive mental health may be the result of teachers’ informed perceptions and positive attitudes on mental health literacy.